Experiences of Women in the Labour Room: The Untold Story - Emmanuel Dziwornu; Belinda Kpodo; Ophelia Anarfi; Enyonam Adzato; Anita Dartey (Patient Experience Journal)
Background: Childbirth experiences are some of the most sensitive indicators of the utilisation of health facilities. Women who go through the child-birthing process are reported to be faced with a range of experiences. Aim: This study described women's experiences in the labour room. Methods: The study employed a qualitative research approach with a descriptive design. Purposive sampling was used in this study and data saturation was reached after the 18th participant. In-depth interviews were used to obtain information from recently delivered women. Interviews were audio recorded and transcribed verbatim. Thematic content analysis (TCA) was done and the results were presented as narratives with quotes to support each theme. Overall, four main themes and twelve sub-themes emerged from this study. Findings: Overall, three (3) main themes and ten (10) sub-themes emerged from this study. This study reveals that prenatal experiences were pleasant and supportive. However, postnatal experiences were compromised by neglect, discrimination, and unresponsiveness. Conclusion: The context of birth affects a woman's natural response to labour and childbirth. The effects have long-term implications for both clinical and emotional outcomes such as a woman's sense of competence, adaptability to parenthood, confidence, and initiation of breastfeeding.